Effects of Sorafenib, a Tyrosin Kinase Inhibitor, on Adrenocortical Cancer - Cerquetti, Lidia; Bucci, Barbara; Raffa, Salvatore; Amendola, Donatella; Maggio, Roberta; Lardo, Pina; Petrangeli, Elisa; Torrisi, Maria Rosaria; Toscano, Vincenzo; Pugliese, Giuseppe; Stigliano, Antonio (Frontiers in Endocrinology, 2021)
The lack of an effective medical treatment for adrenocortical carcinoma (ACC) has prompted the search for better treatment protocols for ACC neoplasms. Sorafenib, a tyrosine kinase inhibitor has exhibited effectiveness in the treatment of different human tumors. Therefore, the aim of this study was to understand the mechanism through which sorafenib acts on ACC, especially since treatment with sorafenib alone is sometimes unable to induce a long-lasting antiproliferative effect in this tumor type. The effects of sorafenib were tested on the ACC cell line H295R by evaluating cell viability, apoptosis and VEGF receptor signaling which was assessed by analyzing VE-cadherin and β-catenin complex formation. We also tested sorafenib on an in vitro 3D cell culture model using the same cell line. Apoptosis was observed after sorafenib treatment, and coimmunoprecipitation data suggested that the drug prevents formation VEGFR-VE-cadherin and -catenin proteins complex. These results were confirmed both by ultrastructural analysis and by a 3D model where we observed a disaggregation of spheres into single cells, which is a crucial event that represents the first step of metastasis. Our findings suggest that although sorafenib induces apoptotic cell death a small portion of cells survive the treatment and have characteristics of a malignancy. Based on our data we recommend against the use of sorafenib in patients with ACC.